Inovasi Produk Brownies Dengan Bahan Tambahan Emping Terhadap Daya Terima Konsumen di Papa Cookies Cake & Bakery Shop Yogyakarta - Anidya Ayu Safitri; Agus Solikhin; Alip Suroto (Jurnal Pariwisata Indonesia, 2019)
This study aims to determine how innovative brownie products with emping additives are to the consumer's acceptance of Papa Cookies Cake and Bakery. The type of research used is descriptive qualitative to obtain information about brownie product innovation which includes raw materials, recipe formulations and packaging on consumer acceptability. The method used to collect data is through document studies, interviews and observations. Descriptive data analysis techniques. The results showed that the innovation of brownies with emping additives in Papa Cookies Cake and Bakery, among others, obtaining good raw materials by cooperating with trusted suppliers and guaranteed quality quality, controlling raw materials with a first in first out system, how to maintain standardization of brownie recipes with additional ingredients emping in Papa cookies Cake and Bakery so that the taste does not change, that is by following the standard recipe book. The things that must be considered in making brownies with crackers additives are choosing fresh eggs, good butter, and not too long roasting. Packaging with contrasting and bright colors and highlighting the symbol of the halal can attract consumers. The conclusion in this study is that the innovation of brownies products with emping additives made by Papa Cookies Cake and Bakery can be accepted by consumers.